ANALISIS KEPUASAN PENGGUNA DENGAN SISTEM CHATBOT PEMESANAN MAKANAN DAN MINUMAN VIA TELEGRAM DI RESTORAN - Arif, Ariobimo; Sudarma, Made; Shandyasa, I Wayan (Jurnal SPEKTRUM; Vol 11 No 1 (2024): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2024.v11.i01.p13, 2024)
In the era of technological advancement, the utilization of Chatbots for food and beverage menu ordering through the Telegram Bot platform emerges as an intriguing alternative to enhance customer experiences in the Food and Beverage industry. This research aims to analyze user satisfaction with the Chatbot implementation using the Heuristic method. In this implementation, the Chatbot is supported by Natural Language Processing (NLP) with a focus on customer satisfaction analysis. The Heuristic method serves as the primary evaluation tool to measure aspects such as service speed, user-friendliness, and information clarity. Analysis results reveal positive user responses to the Chatbot, indicating a high level of satisfaction in system usage. These findings support the notion that employing Chatbots with the Heuristic method can deliver a satisfying experience for customers in food and beverage menu ordering. Practical implications of this research can assist restaurants in enhancing service and efficiency through Chatbot implementation that considers user satisfaction aspects measured by the Heuristic method.